The Financial Literacy, Investment Knowledge, Investment Motivation on Investment Interest in the Capital Market Using Bibit and Ajaib Applications (Study on Faculty of Economics and Business Students at Bhayangkara Jakarta Raya University) - Rizky Ananda Sari Putri Utami (Sekolah Tinggi Manajemen IPMI, 2022)
This study aims to obtain information related to the influence of financial literacy, investment knowledge, and investment motivation on investment interest in the capital market through Bibit and Ajaib applications. This study applies a quantitative method with a causal associative research design technique where the design in this study is used to find whether or not there is a relationship between variables that are causal as a factor to something and how big the level of relationship and influence is. In this study, the population that the researchers used were undergraduate students on Faculty of Economics and Business Students at Bhayangkara Jakarta Raya University who knew or used the Bibit or Ajaib applications. This study applies a tool to analyze data using SPSS 26. The results obtained in this research on the regression test show that financial literacy does not result in an influence on investment interest, but investment knowledge and investment motivation result in an influence on investment interest and in the 47.8% summary model can be described by the variables in this research.